First Experience in Management of Coronavirus Disease 2019 (COVID-19) in Kidney Transplant Patient – Case Report - Severova Andreevska, Galina; Nikolov, Igor; Trajceska, Lada; Gjorgjievski, Nikola; Cana, Fadil; Demiri, Ilir; Stevanovic, Milena; Rambabova Bushljetikj, Irena; Spasovski, Goce (Scientific Foundation SPIROSKI, 2020)
BACKGROUND: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has recently emerged in the world. There are limited data describing the clinical progression of COVID-19 in transplanted patients. In the general population, clinical presentation ranges from asymptomatic infection to severe pneumonia and may also develop renal failure. In kidney transplant (KT) patients, management of these patients was mainly based on anecdotal experience. CASE REPORT: We report our first experience of KT patients with COVID-19. A 49-year-old male with KT in 2017 presented on March 20, 2020, with fever, weakness, smell loss, chest pain, and caught. On chest X-ray, he presented ground-glass opacities and bilateral pneumonia. There was a slight progression to acute hypoxic respiratory failure. We reduced immunosuppression therapy and since we suspected seasonal flu, we applied available antiviral oseltamivir till confirmation of RNA sequence of the SARS-CoV-2 virus. Moreover, we applied azithromycin and broad spectrum of antibiotics as well as an anticoagulant therapy. Graft function remained stable during 14 days of hospitalization. The patient clinically improved with decreasing oxygen requirements and manifested clinical recovery. After two negative PCR test, he was discharged and immunosuppression therapy was returned to previous. CONCLUSION: This case highlights the importance of earlier outpatient hospitalization and testing which may improve COVID-19 outcomes among transplanted patients.